Loss‐of‐function of miR‐142 by hypermethylation promotes TGF‐β‐mediated tumour growth and metastasis in hepatocellular carcinoma. (30th September 2017) - Yu, Qiangfeng; Xiang, Leyang; Yin, Libo; Liu, Xincheng; Yang, Dinghua; Zhou, Jianyin
Abstract: Objectives: Hypermethylation‐induced epigenetic silencing of tumour suppressor genes (TSGs) are frequent events during carcinogenesis. MicroRNA‐142 (miR‐142) is found to be dysregulated in cancer patients to participate into tumour growth, metastasis and angiogenesis. However, the tumour suppressive role of miR‐142 and the status of methylation are not fully understood in hepatocellular carcinoma (HCC). Methods: Hepatocellular carcinoma tissues and corresponding non‐neoplastic tissues were collected. The expression and function of miR‐142 and TGF‐β in two HCC cell lines were determined. The miRNA‐mRNA network of miR‐142 was analysed in HCC cell lines. Results: We found that the miR‐142 expression was reduced in tumour tissues and two HCC cell lines HepG2 and SMMC7721, which correlated to higher TNM stage, metastasis and differentiation. Moreover, miR‐142 was identified to directly target and inhibit transforming growth factor β (TGF‐β), leading to decreased cell vitality, proliferation, EMT and the ability of pro‐angiogenesis in TGF‐β‐dependent manner. Interestingly, the status of methylation of miR‐142 was analysed and the results found the hypermethylated miR‐142 in tumour patients and cell lines. The treatment of methylation inhibitor 5‐Aza could restore the expression of miR‐142 to suppress the TGF‐β expression, which impaired TGF‐β‐induced tumour growth. Conclusion: These findings implicated that miR‐142 was a tumour suppressor gene in HCC and often hyermethylated to increase TGF‐β‐induced development of hepatocellular carcinoma.